Age-specific reference ranges of prostate-specific antigen in the elderly of Amirkola: A population-based study - Reza, Hosseini Seyed (Asian J Urol, 2021)
OBJECTIVE: To determine the age-specific reference ranges of prostate-specific antigen (PSA) in the older men in the city of Amirkola. METHODS: This cross-sectional study is a part of Amirkola Health and Ageing Project (AHAP) which has been conducted as a cohort study since 2011 in Amirkola, a city in northern Iran. The demographic information of all men aged 60 and older were collected through questionnaires and interviews and the PSA measurements were performed using ELISA and Diametra kit. The acquired data were analyzed afterwards. RESULTS: A number of 837 elderly men with a mean age of 69.99±7.72 years participated in this study. The serum PSA level (95th percentile) was determined to be 0.9 (0–4.89) ng/mL in the age group of 60–64 years, 1.1 (0–4.88) ng/mL in the age group of 65–69 years, 0.93 (0–9.01) ng/mL in the age group of 70–74 years, 1.3 (0–7.95) ng/mL in the age group of 75–79 years, 1.9 (0–11.98 ng/mL) in the age group of 80–84 years, and 1.45 (0–33.17) ng/mL in the 85 and older group. The serum PSA level was significantly correlated with age (p=0.000). CONCLUSION: This study indicated that there is a direct correlation between the age and serum PSA levels. The use of age-specific reference range could guide clinicians on the incidence of prostate cancer in this population and perhaps reduce the number of unnecessary tests in this population group.